2020
DOI: 10.3892/etm.2020.8880
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin induces apoptosis and counteracts cisplatin‑induced chemoresistance via Mcl‑1 in ovarian cancer cells

Abstract: Ovarian cancer (OC) is one of the prominent causes of mortality in female patients diagnosed with gynecologic malignancies. While it has previously been demonstrated that apigenin inhibits cell growth in colon and breast cancer cells, the effect of apigenin in OC cells is not fully understood. Therefore, the aim of the present study was to investigate the impact of apigenin on cell death and resistance to cisplatin in OC cells. It was found that apigenin inhibited proliferation, hindered cell cycle progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…Our results were consistent with the results of other previous studies, in which Api was shown to induce apoptosis in different cancer cells, such as BC [24][25][26][27][28]35], ovarian cancer [45], and lung cancer [46]. Api exerts apoptotic effects through increases in the expression of p53 and the ratio of Bax/Bcl2, activation of caspases and cleavage of PARP [44][45][46]. Since the cell number is the result of cell proliferation, survival and cell death, the apoptotic effects of Api, accompanied by our results regarding the cell cycle, can explain the anti-proliferative effects of Api observed in our cell proliferation assays.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results were consistent with the results of other previous studies, in which Api was shown to induce apoptosis in different cancer cells, such as BC [24][25][26][27][28]35], ovarian cancer [45], and lung cancer [46]. Api exerts apoptotic effects through increases in the expression of p53 and the ratio of Bax/Bcl2, activation of caspases and cleavage of PARP [44][45][46]. Since the cell number is the result of cell proliferation, survival and cell death, the apoptotic effects of Api, accompanied by our results regarding the cell cycle, can explain the anti-proliferative effects of Api observed in our cell proliferation assays.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, we showed that Api induced apoptosis in both the MCF-7/Ctrl cells and MCF-7/Akt cells. Our results were consistent with the results of other previous studies, in which Api was shown to induce apoptosis in different cancer cells, such as BC [24][25][26][27][28]35], ovarian cancer [45], and lung cancer [46]. Api exerts apoptotic effects through increases in the expression of p53 and the ratio of Bax/Bcl2, activation of caspases and cleavage of PARP [44][45][46].…”
Section: Discussionsupporting
confidence: 93%
“…Apigenin (APG) is a natural bioflavonoid present in fruits and vegetables and has anti-tumor activity against different cancers. APG administration is of importance in suppressing cisplatin resistance of ovarian cancer cells via apoptosis induction and Mcl-1 down-regulation [183]. In increasing DOX cytotoxicity, APG inhibits DNA repair of breast cancer cells [184].…”
Section: Nrf2 In Doxorubicin Resistancementioning
confidence: 99%
“…In addition, apigenin reduced mitochondrial transmembrane potential and elevated caspase-3/cleaved caspase-3 and Bax/Bcl-2 ratios in both cell types. Quantitative reverse transcription PCR and Western blotting results demonstrated that apigenin significantly downregulates Mcl-1 transcription and translation levels in SKOV3 and SKOV3/DDP cells, which is responsible for its cytotoxic functions and chemosensitizing effects [61]. Thus, the compounds identified in propolis and geopropolis extracts have already been studied by different researchers, demonstrating their antitumor potential.…”
Section: Chemical Identification Of Antitumor Extracts From Propolis and Geopropolismentioning
confidence: 93%